Saquinavir-Piperine Eutectic Mixture: Preparation, Characterization, and Dissolution Profile - Fandaruff, Cinira (2023)
The dissolution rate of the anti-HIV drug saquinavir base (SQV), a poorly water-soluble and extremely low absolute bioavailability drug, was improved through a eutectic mixture formation approach. A screening based on a liquid-assisted grinding technique was performed using a 1:1 molar ratio of the drug and the coformers sodium saccharinate, theobromine, nicotinic acid, nicotinamide, vanillin, vanillic acid, and piperine (PIP), followed by differential scanning calorimetry (DSC). Given that SQV-PIP was the only resulting eutectic system from the screening, both the binary phase and the Tammann diagrams were adapted to this system using DSC data of mixtures prepared from 0.1 to 1.0 molar ratios in order to determine the exact eutectic composition. The SQV-PIP system formed a eutectic at a composition of 0.6 and 0.40, respectively. Then, a solid-state characterization through DSC, powder X-ray diffraction (PXRD), including small-angle X-ray scattering (SAXS) measurements to explore the small-angle region in detail, Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and a powder dissolution test were performed. The conventional PXRD analyses suggested that the eutectic mixture did not exhibit structural changes; however, the small-angle region explored through the SAXS instrument revealed a change in the crystal structure of one of their components. FT-IR spectra showed no molecular interaction in the solid state. Finally, the dissolution profile of SQV in the eutectic mixture was different from the dissolution of pure SQV. After 45 min, approximately 55% of the drug in the eutectic mixture was dissolved, while, for pure SQV, 42% dissolved within this time. Hence, this study concludes that the dissolution rate of SQV can be effectively improved through the approach of using PIP as a coformer.